2013
DOI: 10.1128/aac.02290-12
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Microscopic Observation of Candida Biofilm Development and Effects Due to Micafungin and Fluconazole

Abstract: dTo understand the process of Candida biofilm development and the effects of antifungal agents on biofilms, we analyzed realtime data comprising time-lapse images taken at times separated by brief intervals. The growth rate was calculated by measuring the change of biofilm thickness every hour. For the antifungal study, 5-h-old biofilms of Candida albicans were treated with either micafungin (MCFG) or fluconazole (FLCZ). MCFG began to suppress biofilm growth a few minutes after the initiation of the treatment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 16 publications
1
27
0
2
Order By: Relevance
“…These investigators reported that all Candida isolates (except C. tropicalis ) displayed a paradoxical effect more frequently when grown as biofilms compared to planktonic cells. A paradoxical effect of echinocandin can also be discerned in the study by Kaneko et al ( 130 ), who compared the antibiofilm activity of micafungin against early-phase biofilms after continued exposure for up to 24 h (described above). These investigators reported that after 15 h of incubation, micafungin-exposed biofilms exhibited some regrowth, compared to exposure for 5 min, when almost all the biofilm was inhibited.…”
Section: Antifungal Susceptibility Profile Of Candida Biofilmsmentioning
confidence: 86%
See 1 more Smart Citation
“…These investigators reported that all Candida isolates (except C. tropicalis ) displayed a paradoxical effect more frequently when grown as biofilms compared to planktonic cells. A paradoxical effect of echinocandin can also be discerned in the study by Kaneko et al ( 130 ), who compared the antibiofilm activity of micafungin against early-phase biofilms after continued exposure for up to 24 h (described above). These investigators reported that after 15 h of incubation, micafungin-exposed biofilms exhibited some regrowth, compared to exposure for 5 min, when almost all the biofilm was inhibited.…”
Section: Antifungal Susceptibility Profile Of Candida Biofilmsmentioning
confidence: 86%
“…Aminocandin, a newer echinocandin, has also been shown to exhibit anti-biofilm properties ( 129 ). Recently, Kaneko et al ( 130 ) performed time-lapse microscopic observation of the effect of micafungin (an echinocandin) and fluconazole on Candida biofilms formed for up to 24 h on silicon disks in RPMI medium under flow (20 ml/h). These investigators showed that Candida biofilms grew at a uniform rate in the absence of drugs (17.2 ± 1.3 μm/h) and observed detachment of clusters of fungal cells from the hyphal tips in mature biofilms.…”
Section: Antifungal Susceptibility Profile Of Candida Biofilmsmentioning
confidence: 99%
“…One of the final stages of BF production is its maturation through excretion of matrix material . Use of VRC for the treatment of C. albicans cells in BF results in the formation of cells with altered structure and function of plasma membranes .…”
Section: Discussionmentioning
confidence: 99%
“…One of the final stages of BF production is its maturation through excretion of matrix material. [18][19][20] Use of VRC for the treatment of C. albicans cells in BF results in the formation of cells with altered structure and function of plasma membranes. 21 In our study, treatment of intermediate BFs with VRC resulted in down-regulation of SUN41 and BGL2 genes, whereas the opposite effect was observed when mature biofilms were treated with VRC.…”
Section: Discussionmentioning
confidence: 99%
“…albicans biofilm formation characterized as a series of sequential steps: (1) biofilm formation begins with adherence step which cell-wall protein-mediated adherence of yeast cells to a surface (2) Initiation step, the yeast cells proliferate across the surface and produce elongated projections that grow into filamentous forms, including hyphae or/ and pseudohyphae (3) Maturation step extracellular matrix accumulates as the biofilm matures, and high-level drug resistance is also acquired Finally, (4) non-adherent yeast cells are released from the biofilm into the surrounding medium (dispersal step). While these steps may occur concurrently rather than sequentially during natural biofilm formation [12,13].…”
Section: Introductionmentioning
confidence: 99%